Retrograde type A aortic dissection during or after thoracic endovascular aortic repair: a single center 16-year experience - Wang, Guo-quan; Qin, Ya-fei; Shi, Shuai-tao; Zhang, Ke-wei; Zhai, Shui-ting; Li, Tian-xiao (Frontiers in Cardiovascular Medicine, 2023)
Objective This article aims to investigate the incidence rate of retrograde type A aortic dissection (RTAD) and the risk factors of RTAD in relation to thoracic endovascular aortic repair (TEVAR). Methods Patients with thoracic aortic disease who underwent TEVAR at Henan Provincial People’s Hospital from January 2004 to December 2019 were enrolled in the present research. The risk factors associated with RTAD following TEVAR using univariate and multiple logistic regression analyses. Results During the study period, A total of 1688 TEVAR patients were included in this study, and of these, 1592 cases were included in the type B aortic dissection (TBAD) group, and 96 cases were included in the non-TBAD group. There were 1230 cases of aortic dissection and 362 cases of aortic intramural hematoma and/or penetrating ulcer in the TBAD group. The non-TBAD group included 68 cases of thoracic aortic aneurysm, 21 cases of thoracic aortic pseudoaneurysm, and seven cases of congenital aortic coarctation. The overall incidence rate of RTAD was 1.1% (18/1688) in patients, all of which occurred in the TBAD group. The cohort comprised 18 RTAD patients with an average age of 56.78, consisting of 13 males and 5 females. Among them, 13 individuals exhibited hypertension. Ten instances happened within the TEVAR perioperative period, including two cases during the surgery, six cases occurred within three months, two cases occurred after one year, and the longest interval was 72 months following TEVAR. The new entry position for RTAD was identified as the proximal region of the stent graft (SG) in 13 patients, while in five cases, the entry site was more than 2 cm away from the proximal region of the SGMultivariate logistic regression analysis revealed that the SG oversizing ratio is a relevant risk factor for RTAD. However, ascending aortic diameter, aortic arch type, SG type, and anchored region were not directly related to the occurrence of RTAD. Conclusion RTAD is a rare yet catastrophic complication. It could occur both during the procedure, early and late postoperative periods. Maintaining an appropriate SG oversizing ratio is crucial to minimize the risk of RTAD.